Effects of Postharvest Storage Temperature on Physical Characteristic, Phenolic Compounds, and Antioxidant Activity of Cocoa Pod Husk - Salfi, Wa Ode Nurhidayah; Ningrum, Andriati; Supriyadi, Supriyadi (Department of Agrotechnology, Universitas Muhammadiyah Yogyakarta, 2024)
Cocoa pod husk (CPH) is a good source of bioactive components such as phenolic compounds, which are known to have potential as antioxidants. Research on the effects of postharvest storage conditions on bioactive compounds of CPH is still limited. Therefore, this study aimed to evaluate the impact of postharvest storage temperature (20, 30, and 40 °C) and time on the physical characteristics, phenolic compounds, and antioxidants of CPH. The results indicated that storage for nine days reduced the color and moisture content of CPH while the texture hardened (especially at 20 and 40 °C). Total phenolic compounds (TPC) increased to 97.9% when CPH was stored at 20 °C for nine days, which was associated with an increase in catechin content and antioxidant activity. The first-order kinetic model was suitable for predicting the kinetics of changes in color, moisture content, hardness, TPC, and DPPH. The calculated Ea values indicated that the storage temperature caused the color of CPH to change easily to brown and the catechin and caffeic acid compounds to form easily. Overall, it is better to store CPH at 20 °C for nine days to increase the quality.